1996
DOI: 10.1099/00207713-46-2-466
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of a Polycyclic Aromatic Hydrocarbon-Metabolizing Bacterium, Beijerinckia sp. Strain B1, as Sphingomonas yanoikuyae by Fatty Acid Analysis, Protein Pattern Analysis, DNA-DNA Hybridization, and 16S Ribosomal DNA Sequencing

Abstract: A bacterium isolated from a polluted stream, capable of metabolizing biphenyl, naphthalene, phenanthrene, and higher-molecular-weight polycyclic aromatic hydrocarbons (D. Gibson, V. Mahadevan, D. Jerina, H. Yagi, and H. Yeh, Science 189:295-297, 1975), was previously identified as Beijerinckiu sp. strain B1. In this investigation, 16s rRNA gene sequencing, biochemical tests, fatty acid methyl ester analysis, polyacrylamide gel electrophoresis of protein, and DNA-DNA hybridization were used to determine the tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 2 publications
0
44
0
Order By: Relevance
“…32,50,52) . This strain was later reclassified as Sphingomonas yanoikuyae on the basis of phylogenetic and chemotaxonomic data 104) . The genus Sphingomonas has recently been split into four genera with three new generic names, Novosphingobium, Sphingobium and Sphingopyxis 180) .…”
Section: Aerobic Degradation Processes and Biodiversity Of Bacteria Imentioning
confidence: 99%
“…32,50,52) . This strain was later reclassified as Sphingomonas yanoikuyae on the basis of phylogenetic and chemotaxonomic data 104) . The genus Sphingomonas has recently been split into four genera with three new generic names, Novosphingobium, Sphingobium and Sphingopyxis 180) .…”
Section: Aerobic Degradation Processes and Biodiversity Of Bacteria Imentioning
confidence: 99%
“…It was later found that this group of bacteria could also be isolated from natural sources, such as soil, rhizosphere, sediment, freshwater and marine environments [26]. Many Sphingomonas strains isolated from the environment possess broad catabolic capabilities towards recalcitrant organic pollutants, which include dibenzo-p-dioxin and dibenzofuran [27], carbofuran [6], hexachlorocyclohexane [9], chlorinated biphenyls [24], polychlorophenols [11,16], 2,4-dichlorophenoxyacetic acid [10], halogenated diphenyl ethers [21], and single-ring aromatic and polyaromatic hydrocarbons [7,13]. Despite the catabolic diversity of the genus Sphingomonas, its members are related phylogenetically.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study showed that the genes and gene orders for aromatic hydrocarbon degradation of strain DJ77 T were strikingly similar to the corresponding genes of Sphingomonas species, such as Sphingomonas paucimobilis EPA505, Sphingomonas yanoikuyae B1, ' Sphingomonas agrestis ' HV3 and Sphingomonas aromaticivorans F199 (Mueller et al, 1990 ;Kim, 1996 ;Yrja$ la$ et al, 1997 ;Romine et al, 1999). The members of the genus Sphingomonas have been reported to degrade various aromatic hydrocarbons (Wittich et al, 1992 ;Ka et al, 1994 ; Fredrickson et al, 1995 ;Khan et al, 1996). In this study, we applied a polyphasic approach to identify strain DJ77 T .…”
Section: Introductionmentioning
confidence: 99%